The relationship between macroeconomic variables and non performing loan: evidence from selected ASEAN countries - Noor Azean Azdzila, Zulkifli (2017)
High non-performing loans (NPLs) create the problem for the banking sector as financial intermediary and signal of banking crisis. Many attempts have been made to investigate the determinant of NPLs yet the crucial issue has remained unexplained. The motivation of this research paper is to study the relationship between macroeconomic variables and global financial crisis on NPLs in the Association of Southeast Asian Nations (ASEAN) countries. Using panel data of 6 countries of the ASEAN for 2005-2015, the model of NPL is regressed using Generalized Method of Moment (GMM) method. Based on the empirical finding reveals that the inflation, gross domestic product (GDP) and global financial crisis significantly effect NPL. In the area of policy implications, the policymaker should focus and reengineering the institutions together with these indicators could reduce the probability of NPLs in bank of ASEAN countries.